EXPLORING THE EU ARTIFICIAL INTELLIGENCE ACT: PERSPECTIVES OF PROFESSIONALS IN FINLAND - Mensah, Benjamin (2024)
As artificial intelligence continues to find its way into our lives, with or without our consent. There has been the need to put safeguards in place to ensure it operates within acceptable standards. Governments and organizations want to ensure the rights of citizens are protected over business interests, hence the introduction of the European Union artificial intelligence act. The European Union's Artificial Intelligence Act (EU AI Act) represents a significant regulatory effort to govern the development and deployment of AI technologies across member states. This master’s thesis researches the perspective of professionals in Finland on the EU AI act using qualitative research approach including semi-structured interviews and conventional content analysis. Key themes emerged, highlighting the act's focus on ethics, transparency, accountability, and bias mitigation. The study interviewed 9 professionals in Finland whose work involved AI and had some knowledge about the regulation. The findings suggest that while the EU AI Act is viewed as a critical step towards embedding ethical AI practices and fostering public trust, the study also revealed concerns about the potential impact on innovation and the variability in awareness and understanding of the Act among professionals. These insights contribute to the broader discourse on AI regulation, emphasizing the need for continuous policy development, technological innovation, and interdisciplinary collaboration to address evolving challenges. Future research should consider larger, more diverse professionals, the use of surveys, and comparative analyses across different fields like healthcare, legal, manufacturing and consumer services to further understand the Act's impact and effectiveness. Keywords: Artificial Intelligence, EU AI Act, bias, ethics, transparency